Features of wave transformation by a permeable breakwater - Voskoboinick, Volodymyr Anatoliyovych; Voskoboinyk, Oleksandr Anatoliyovych; Voskobiinyk, Andriy Volodymyrovych; Kharchenko, Anatolii Grygorovych; Trudenko, Denys Volodymyrovych (Національний технічний університет "Харківський політехнічний інститут", 2025)
The influence of the permeability of a breakwater on the wave transformation is studied. It is assumed that the vertical breakwater, in contrast to an absolutely rigid one, is characterized by a finite permeability and can absorb the energy of incoming incident waves. In this regard, the propagation of surface gravity waves in a rectangular coordinate system is investigated. Traditional realized examples of wave energy selection and their mathematical analysis are given. From the law of conservation of energy upon reflection from vertical walls follows the dependence for the reflection coefficient as a function of the transmission coefficient. The results of experimental studies of the propagation of surface gravity waves and their interaction with absorbing walls are presented. The dependences of the coefficients of reflection and transmission of the wave, as well as the coefficients of dissipation of wave energy depending on the permeability of the vertical wall, the depth of the flow, and the length of the incident wave are obtained. The integral and spectral characteristics of the wave field and pressure fluctuations on the streamlined surface of a permeable breakwater are presented. Досліджено вплив проникності хвилелому на трансформацію хвилі. Передбачається, що вертикальний хвилелом, на відміну від абсолютно жорсткого, характеризується кінцевою проникністю і може поглинати енергію набігаючих хвиль. У зв’язку з цим досліджено поширення поверхневих гравітаційних хвиль у прямокутній системі координат. Наведено традиційні реалізовані приклади відбору енергії хвилі та їх математичний аналіз. Із закону збереження енергії при відбиванні від вертикальних стінок випливає залежність для коефіцієнта відбиття як функції коефіцієнта проникнення. Наведено результати експериментальних досліджень поширення поверхневих гравітаційних хвиль та їх взаємодії з поглинаючими стінками. Отримано залежності коефіцієнтів відбиття і проникнення хвилі, а також коефіцієнтів дисипації енергії хвилі в залежності від проникності вертикальної стінки, глибини потоку і довжини початкової хвилі. Наведено інтегральні та спектральні характеристики поля хвиль і коливань тиску на обтічній поверхні водопроникного хвилелому.
Особливості трансформації хвиль проникним хвилеломом
Keywords: wave transformation; permeable breakwater; numerical and physical simulation; wave reflection and transmission; wave energy dissipation; трансформація хвиль; проникний хвилелом; чисельне та фізичне моделювання; відбиття та проникнення хвиль; дисипація хвильової енергії